Rates of early complications and mortality in patients older than 80 years of age after surgical treatment of acute traumatic spinal fractures: ankylosing spondylitis versus osteoporosis - Ishak, Basem; Frieler, Sven; Rustagi, Tarush; Glinski, Alexander von; Blecher, Ronen; Norvell, Daniel C.; Unterberg, Andreas; Strot, Sarah; Roh, Jeffrey; Hart, Robert A.; Oskouian, Rod; Chapman, Jens R. (Neurosurgical focus, 2021)
OBJECTIVE The purpose of this retrospective cohort study was to analyze the early complications and mortality associated with multilevel spine surgery for unstable fractures in patients older than 80 years of age with ankylosing spondylitis and to compare the results with an age- and sex-matched cohort of patients with unstable osteoporotic fractures. METHODS A retrospective review of the electronic medical records at a single institution was conducted between January 2014 and December 2019. Patient demographics, surgical characteristics, complications, hospital course, and 90-day mortality were collected. Comorbidities were stratified using the age-adjusted Charlson Comorbidity Index (CCI). RESULTS Among 11,361 surgically treated patients, 22 patients with ankylosing spondylitis (AS group) and 24 patients with osteoporosis (OS group) were identified. The mean ages were 83.1 ± 3.1 years and 83.2 ± 2.6 years, respectively. A significant difference in the mean CCI score was found (7.6 vs 5.6; p < 0.001). Multilevel posterior fusion procedures were conducted in all patients, with 6.7 ± 1.4 fused levels in the AS group and 7.1 ± 1.1 levels fused in the OS group (p > 0.05). Major complications developed in 10 patients (45%) in the AS group compared with 4 patients (17%) in the OS group (p < 0.05). The 90-day mortality was 36% in the AS group compared with 0% in the OS group (p < 0.001). CONCLUSIONS Patients older than 80 years of age with AS bear a high risk of adverse events after multilevel spinal fusion procedures. The high morbidity and 90-day mortality should be clearly discussed and carefully weighed against surgical treatment.
Gesehen am 09.02.2022